2021
DOI: 10.1002/ece3.8235
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of ecological differences? Stress responses of sympatric Alpine chamois and red deer to weather, forage quality, and human disturbance

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 71 publications
3
19
0
Order By: Relevance
“…FCM analyses were conducted using an 11-oxoetiocholanolone-17-CMO:BSA enzyme immunoassay (EIA, measures group of FCM with a 5 -3 -ol-11-one structure; Möstl et al 2002 ), previously validated for red deer and chamois (Anderwald et al 2021 ; Huber et al 2003 ). These analyses require samples to be fresh and wet.…”
Section: Methodsmentioning
confidence: 99%
“…FCM analyses were conducted using an 11-oxoetiocholanolone-17-CMO:BSA enzyme immunoassay (EIA, measures group of FCM with a 5 -3 -ol-11-one structure; Möstl et al 2002 ), previously validated for red deer and chamois (Anderwald et al 2021 ; Huber et al 2003 ). These analyses require samples to be fresh and wet.…”
Section: Methodsmentioning
confidence: 99%
“…These values were also compared with our previous baseline study and it was found that the current values are equivalent or within the baseline values for both EIAs, but greater similarity is seen especially with the values detected by the 50c EIA (50c EIA: min = 2.2; max = 131.1; median = 16.5; cortisol EIA: min = 0.3; max = 33.9; median = 5.9) [ 33 ]. Many studies have established baseline values [ 48 ] of stress hormones before analysing the effect of climate change and other anthropogenic stressors on wildlife [ 41 , 49 , 50 ]. Previous, and current, results give us confidence that our baseline values can be used in this and future studies to detect stress in koalas.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sampling plots close to the hiking trail could be browsed during visitor-free periods at dusk, night and dawn. Additionally, Anderwald et al [39] analyzed fecal glucocorticoid metabolite levels of chamois and red deer in the SNP and showed that visitor densities were apparently not a strong stressor. Furthermore, the hiking trails are mainly located at the base of the valley and hence this predictor correlates strongly with elevation (correlation coefficient of 0.74, Table S3), thus part of the effect of the distance to the next hiking trail on the probability of browsing may be explained by elevation.…”
Section: Factors Affecting the Probability Of Browsingmentioning
confidence: 99%